Limits of Enjoyment of Human Rights in the System of the European Social Charter - Jasudowicz, Tadeusz (Polish Review of International and European Law, 2018)
The article presents a detailed discussion of the derogation of commitments and the limitation of the use of human rights in the European Social Charter system. Some situations in which social rights can be subject to limitations have been discussed in specific examples. In addition, the article contains numerous references to jurisprudence along with the comments and comments of the author who takes up the polemic.